A PROBLEMATIC MISSIONARY TEXT: ‟JOHN 20:23” AND THE ISSUE OF THE TRANSLATION OF THE TWO MAIN CLAUSES (‟ἀφίενται” AND ‟kεκράτηνται”) / UN TEXT MISIONAR PROBLEMATIC: ‟IOAN 20, 23” ȘI ACURATEȚEA TRADUCERII CELOR DOUĂ VERBE PRINCIPALE (‟ἀφίενται” ȘI ‟κεκράτην) - VARGA, Cătălin (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2015)
One of the most central theological themes of Orthodoxy is sacerdotalism, the mystery of priesthood and its roots growing from this Johannine verse, in which apostles are sent to mission after they were invested with power to forgive the sins. The problem that occurs refers to the translation of the perfect that is found in the main clause in both sentences: ἀφίημι (to let go, forgive) and κρατέω (to retain, to grasp), which in some manuscripts of the New Testament (Codex Sinaiticus; Codex Alexandrinus; Codex Bezae) and in a few uncials and critical editions of the Greek New Testament (Westcott and Hort; Nestle’s Greek New Testament), appears to be perfect tense. According to Greek New Testament grammars, the perfect tense pictures a past action, the result of which was present to the speaker or writer. So Jesus warned the disciples that they were to treat as forgiven only those that were already forgiven by God. According to this scenario, their entire mission summarizes the acts of authenticating the things that have already been made for them (in their name) and for the people. Our research deals with this issue, underlines the value of indicative present mood of this two verbs, as we encounter them in the byzantine manuscripts of the New Testament and also in Codex Vaticanus. The large context of the story deals with the action of breathing the Holy Spirit over the disciples, transforming them into a new existence and receiving power by this, to forgive or retain everyone’s sins, that is why I see the perfect tense as the result of a scribal error. The difference between the present ἀφίενται and the perfect ἀφέωνται consist of two letters changed, an error that might have occured among the scribs. Establishing the indicative present of the action is an urgent task for the world of orthodox biblical studies, because according to this prerequisite, our whole missionary agenda earns credits. Una dintre temele centrale ale Ortodoxiei este sacerdotalismul, taina preoției ce reiese din acest text ioaneic, în care apostolii sunt trimiși la misiune, investiți fiind cu puterea de a lega sau dezlega păcatele oamenilor. Problema care se ridică este legată de traducerea celor două perfecte ἀφίημι (a lăsa, a ierta) și κρατέω (a ține), care în unele manuscrise ale Noului Testament (Codex Sinaiticus; Codex Alexandrinus; Codex Bezae), în câteva lecționare și în unele ediții critice (Westcott and Hort; Nestle’s Greek New Testament), apar a fi verbe la perfect. Potrivit gramaticii limbii Noului Testament, perfectul prezintă o acțiune trecută și încheiată pentru observator. Astfel că Iisus îi înștiințează pe apostoli că vor trebui să-i ierte pe toți aceia care au fost deja iertați. Potrivit acestui scenariu, întreaga lor misiune se rezumă la autentificarea acțiunilor care s-au consumat deja în numele lor pentru binefacerea poporului. Cercetarea de față se concentrează asupra acestei problematici, subliniind rolul indicativului prezent al celor două verbe principale precum sunt întâlnite ele în tradiția bizantină a manuscriselor Noului Testament și în Codex-ul Vaticanus. Contextul lărgit al versetului prezintă suflarea Duhului Sfânt peste apostolii prezenți, de către Hristos Cel Înviat, transformându-i pe aceștia într-o creație nouă, specifică post-pascală, oferindu-le prin aceasta puterea și autoritatea necesară de a ierta păcatele. De aceea consider că prezența perfectului în logica acestui text, nu poate fi decât rezultatul unor greșeli ale scribilor. Diferența dintre prezentul ἀφίενται și perfectul ἀφέωνται este dată de schimbarea a două litere în interiorul cuvântului, o eroare care s-ar fi putut înregistra în lumea scribilor Noului Testament. Stabilirea indicativului prezent al acțiunii, devine o sarcină stringentă în lumea ortodoxă a studiilor biblice, deoarece în logica acestei moșteniri patristice, întregul nostru program misionar câștigă credit.